Synthesis and investigation of donor–porphyrin–acceptor triads with long-lived photo-induced charge-separate states. Issue 11 (13th August 2015) - Kelber, Julien B.; Panjwani, Naitik A.; Wu, Di; Gómez-Bombarelli, Rafael; Lovett, Brendon W.; Morton, John J. L.; Anderson, Harry L.
Abstract : The powerful electron donor tetraalkylphenylenediamine (TAPD ) facilitates photo-induced electron transfer, even in a frozen solvent at 10 K, generating a long-lived spin-polarized charge separate state which can be observed by EPR. Abstract : Two donor–porphyrin–acceptor triads have been synthesized using a versatile Suzuki-coupling route. This synthetic strategy allows the powerful donor tetraalkylphenylenediamine (TAPD ) to be introduced into tetraarylporphyrin-based triads without protection. The thermodynamics and kinetics of electron transfer in the new triads are compared with a previously reported octaalkyldiphenyl-porphyrin triad exhibiting a long-lived spin-polarized charge separate state (CSS), from theoretical and experimental perspectives, in both fluid solution and in a frozen solvent glass. We show that the less favorable oxidation potential of the tetraaryl-porphyrin core can be offset by usingC60, as a better electron-acceptor than triptycenenaphthoquinone (TNQ ). TheC60 –porphyrin–TAPD triad gives a spin-polarized charge-separated state that can be observed by EPR-spectroscopy, with a mean lifetime of 16 ms at 10 K, which is longer than in the previously reportedTNQ –porphyrin–TAPD triad, following the predicted trend from calculated charge-recombination rates.